Uma análise dos determinantes dos fluxos de capital de curto prazo para o Brasil - Bernardelli, Alessandro Garcia (2012)
This paper aims to analyze the determinants of entry flows of short-term capital in Brazil from July 1999, based on the traditional push-pull factors, ie, those that refer to conditions that attract domestic resources foreigners to the country (pull) and dealing with adverse conditions in developed countries pushing capital to other economies in search of higher returns (push). To accomplish this analysis employs a model of Structural Vector autoregressive (SVAR), covering the period from July 1999 to December 2011. The results indicate the predominance of the effect on the pull push effect, especially for the price index of the stock market (Bovespa Index) and the Selic interest rate as the domestic variables that most influenced the variance of the inflows of short-term capital Brazil. As regards the external variables the rate of U.S. industrial production had greater variance of capital flows to Brazil that the rate of short-term interest, so that expansions in U.S. production had a positive impact on inflows of short period in Brazil. The predominance of the effect on the pull push effect in Brazil could mean, as already suggested by a few authors, a more robust and less macroeconomic external vulnerability of the country when compared to other periods, eg early and mid-1990s.